2020
DOI: 10.3389/fnins.2020.00422
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Response to Different Tinnitus Treatment

Abstract: Introduction: Tinnitus is a complex symptom requiring a thorough multidisciplinary assessment to construct an individual's tinnitus profile. The Antwerp University Hospital hosts a tertiary tinnitus clinic providing intensive, multidisciplinary tinnitus care in the form of combinational psychological treatment with either Tinnitus Retraining Therapy (TRT)/Cognitive Behavioral Therapy (CBT) or TRT/eye movement desensitization and reprocessing therapy (EMDR), high-definition transcranial direct current stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 57 publications
3
27
0
1
Order By: Relevance
“…Due to the lack of an objective measure and the limited understanding of the mechanisms, research on tinnitus heterogeneity and tinnitus subtypes most often focuses on phenotypic heterogeneity of people with tinnitus; that is measurable traits that vary across individuals with tinnitus. These traits can include both general individual characteristics (not specific to people with tinnitus) such as demographics (e.g., gender) and co-existing conditions (e.g., hearing problems), and tinnitus-specific characteristics such as related to the tinnitus perception or its impact on the affected individual (Langguth et al, 2007;van den Berge et al, 2017;Genitsaridi et al, 2020;Van der Wal et al, 2020).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of an objective measure and the limited understanding of the mechanisms, research on tinnitus heterogeneity and tinnitus subtypes most often focuses on phenotypic heterogeneity of people with tinnitus; that is measurable traits that vary across individuals with tinnitus. These traits can include both general individual characteristics (not specific to people with tinnitus) such as demographics (e.g., gender) and co-existing conditions (e.g., hearing problems), and tinnitus-specific characteristics such as related to the tinnitus perception or its impact on the affected individual (Langguth et al, 2007;van den Berge et al, 2017;Genitsaridi et al, 2020;Van der Wal et al, 2020).…”
Section: Overviewmentioning
confidence: 99%
“…Heterogeneity of tinnitus severity can be assessed not only by the degree of severity, but also by the domains of life that are affected by tinnitus (Hall et al, 2018a). Many studies have investigated associations between tinnitus severity and a number of other phenotypic characteristics such as presence of comorbidities and personality traits (Hoekstra et al, 2014;Van der Wal et al, 2020), but it remains unclear why some people are distressed by tinnitus while others are not.…”
Section: Tinnitus-specific Characteristicsmentioning
confidence: 99%
“…Remarkably, all tinnitus patients were female. This potential gender bias might have influenced the results as it has been suggested that male and female patients respond differently to tinnitus treatments (Van der Wal et al 2020). The most recent study on this topic was done by Zarenoe et al (2017), who compared the effect of hearing aids on working memory, sleep and hearing problems.…”
Section: Resultsmentioning
confidence: 99%
“…Além disso, Andersson et al 25 verificaram uma significativa correlação entre a sensibilidade ansiógena do indivíduo e o grau de gravidade do zumbido, verificando que este aspecto é mais marcante nas mulheres 27 . Van der Wal et al 28 identificaram que as mulheres apresentam níveis mais elevados de incômodo e de ansiedade quando comparado aos homens. Porém, outras pesquisas mostram não existir relação significativa entre o sexo e a severidade do zumbido 20,[29][30] .…”
Section: Discussionunclassified